The Effect of Problem-Based Learning (PBL) on the Critical Thinking Skills of Fourth Grade Students - Sianipar, Ruth Sahanaya; Sijabat, Desi; Simanjuntak, Bernard (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the Effect of Problem Based Learning (PBL) Learning Model on Critical Thinking Skills of Fourth Grade Elementary School Students. This type of research uses quantitative research using experimental methods. This study uses a Pre-Experimental design of the One-Group Pretest-Posttest type. The sample of this study was 25 fourth grade students of HKBP Tomuan Private Elementary School. The Pancasila Education subject obtained scores by fourth grade students of HKBP Tomuan Private Elementary School were: of the 25 students who took the pretest, there were 2 students who completed the pretest and 23 students who did not complete it with an average score of 41.96, and of the 25 students who took the posttest, 25 students who obtained scores above the KKTP with an average score of 83.72. Based on the results of the n-gain test, it states that critical thinking skills are in the moderate criteria with a score of 0.70, it can be concluded that Ha is accepted and H0 is rejected. So it can be concluded that the influence of the Problem Based Learning (PBL) model on the critical thinking skills of fourth grade students of HKBP Tomuan Private Elementary School in the 2025/2026 academic year has increased